Reduction of Hexavalent Chromium to Trivalent Chromium using Sludge from Acetylene Gas Production - Mohd Zainuddin, Nur Ain; Mohamad Sarwani, Nursyahzani; Puasa, Siti Wahidah; Ismail, Kamariah Noor (International Journal of Integrated Engineering, 2022)
Electroplating industry generates harmful anionic heavy metal which is Hexavalent Chromium (Cr6+) that need to be treated before it can be discharged into the environment following accordance to the Environmental Industry (Effluent Regulation) 2009. These Cr6+ ions must be reduced to chromium trivalent (Cr3+) using a reducing agent before undergoing precipitation process for complete removal of (Chromium) Cr component. The common reducing agent is using Sodium Metabisulphite (SMBS). This chemical generates harmful gases which are Hydrogen Sulphide (H2S) and Sulphur Dioxide (SO2). Circular economy practices encouraged by the Department of Environment (DOE) includes repurposing industrial waste, where the undesired by product is seen as a potential resource for other purposes. In this study, sludge from Acetylene gas production is used as a reducing agent. Acetylene production sludge (APS) contains high (Calcium) Ca element and (Ferum) Fe ions that are essential for the reduction of Cr6+ to Cr3+. The analysis of APS characterization is done by XRF and XRD instrument with the result of high Ca and Fe ions with (Ca(OH)2) alkaline properties. The initial concentration of Cr6+ is 3.25 mg/L and total Cr concentration is 1124 mg/L. The highest percentage reduction is 61.5% found at pH 5.51 with the APS dosage of 1.15 ml. For the effect of APS dosing, 100% reduction of Cr6+ is achieved at pH 6.04 with volume of APS used at 1.8 ml.